2021
DOI: 10.3390/microorganisms9112340
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Effects of Chemokine Receptor CXCR3 Deficiency on Immune Responses in the Mouse Brain during Toxoplasma gondii Infection

Abstract: The obligate intracellular parasite Toxoplasma gondii infects warm-blooded animals, including humans. We previously revealed through a whole-brain transcriptome analysis that infection with T. gondii in mice causes immune response-associated genes to be upregulated, for instance, chemokines and chemokine receptors such as CXC chemokine receptor 3 (CXCR3) and its ligand CXC chemokine ligand 10 (CXCL10). Here, we describe the effect of CXCR3 on responses against T. gondii infection in the mouse brain. In vivo as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 77 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Studies have also found that CXCL10, a chemokine released by neurons after brain injury, activates microglia to promote the dissipation of innervated dendrites from the injury site; these effects were obliterated in CXCR3 knockout mice. Other chemokines that have been implicated in microglia activation include C-C chemokine receptor 2 (CCR2), CXC Chemokine Receptor 3 (CXCR3), and chemokine (C-X3-C motif) receptor 1 (CX3CR1) ( 51 ).…”
Section: Membrane Receptors and Pathways In Microglia Activationmentioning
confidence: 99%
“…Studies have also found that CXCL10, a chemokine released by neurons after brain injury, activates microglia to promote the dissipation of innervated dendrites from the injury site; these effects were obliterated in CXCR3 knockout mice. Other chemokines that have been implicated in microglia activation include C-C chemokine receptor 2 (CCR2), CXC Chemokine Receptor 3 (CXCR3), and chemokine (C-X3-C motif) receptor 1 (CX3CR1) ( 51 ).…”
Section: Membrane Receptors and Pathways In Microglia Activationmentioning
confidence: 99%
“…Amplifications were performed using an ABI 7700 Prism Sequence Detector (Bio-Rad, Hercules, CA, United States). The cycle threshold (Ct) values were normalized to the expression levels using the 2 −∆∆Ct method ( Kobayashi et al, 2019 ; Umeda et al, 2021 ). Glyceraldehyde-3-phosphate dehydrogenase ( Gapdh ) was used as the internal control gene after comparison with Actb using RefFinder ( Xie et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Also, an obvious role of the CXCR3 in controlling parasite replication during acute P. chabaudi AS infection has been reported ( Berretta et al, 2019 ). In cases of infection with Toxoplasma gondii , which is closely related to the intracellular protozoan parasite N. caninum , CXCR3 deficiency results in the loss of ability to control intestinal infection ( Cohen et al, 2013 ), increased brain parasite burden ( Umeda et al, 2021 ), and severe embryonic damage in a pregnant model ( Nishida et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%